Implementation dimensions analysis of supervisory objectives in the Division of Negros Occidental in relation to national goals - Guance, Fe Arienda 1928- (1974)
The supervisory objectives of school supervisors in the Division of Negros Occidental in 1971-1972 are congruent with national development goals on human resource development, and social, cultural, economic and political development. Objectives differ in their emphasis by curriculum area with vocational education objectives geared to economic development goals; communication skills, health, science and mathematics, and adult and community education to human resource development; and social studies and the humanities to cultural development. Implementation activities are in harmony despite differences in objectives across curriculum areas. The problems met are poorly trained teachers with unwholesome work attitudes, poor school facilities and equipment and unstable implementation of the course program.